Applying the English Simple Code to Improve Indonesian Students' Communicative Speaking Ability and Their Motivation - Jayaputri, Herlandri Eka; Aziz MT, Muhammad Fahruddin (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2022)
The study aims to improve students’ communicative speaking and motivation using the simple code theory. It was action research. The research procedure consisted of identifying the students’ problems, designing the plans, applying the classroom practice expression (suitable with simple code), observing, and reflecting on each cycle. The subject was 20 students who have the lowest mark in communicative speaking ability and motivation in the pre-observation. Data were collected through observation, tests, interviews, questionnaires, and documentation and were analyzed using the descriptive quantitative, and qualitative. The English Simple Code could improve students’ communicative speaking ability and motivation in grade VIII of SMP Yapis Biak. it is also supported by the result of speaking tests and questionnaires. There are some findings; 1) implementing the classroom practice expression can help the teacher to provide a simpler language for students; 2) teacher-talk and interlanguage-talk are useful for acquiring English at the low-intermediate level; 3) emphasizing the activities of repetition drill and acting from a script can provide a prefabricated routine to prefabricated pattern and develop their fluency simultaneously; 4) teacher‘s role can improve the communicative speaking in performance; 5) delayed feedback is very useful to encourage students’ low affective filter in the learning process, so they got the high confidence and motivation in the second language acquisition. Thus, Theoretically, the English simple code can provide a good contribution to learning strategy in the classroom. Then, the teacher can use classroom practice expression, various activities, and delayed feedback to acquire English as the target language.